(3dhGeY GdGSfI aj GdUdGI Ydi fHi GdQMeI HCSeGA Gddg G dMSfis - (3eMeO Hf UdM Hf edhcI GdJhfSj, Hf edhcI,J (B1226 (3g` s
(3ChdgG (B:s
(3hddg GdGSeGA GdMSfi aGOYhg HgG hbhdhG Udi Ydi SjOfG eMeO jGddg UdGI WjHI jZhUgG JWjH GdCahGg s
(3BNQgG (B:s
(3Udi hSde Ydjg jGddg jG UHhQ UdGI JYe GdESdGe HgeG GdKZhQ GfJgi hdjS hQGA Gddg efJgG s
(3GdfSNI HgG MhGTs
(3fGhdI Jedcs
(3hLYdg eUfag Ydi ChQGO habkG ddCjGe GdeNWhW jTJed Ydi fSNJjf dfaS GdcJGH s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs